Re-Evaluation of Vascular Histogenesis in the Root Tips of Selected Species in the Poaceae Using New Methods: Analysis of the Plerome, Vascular Initials, Pericycle and Late-Maturing Metaxylem Vessels - Yasushi Miki; Susumu Saito; Teruo Niki; Daniel K. Gladish (Plants, 2024)
Serial sectioning and 3D image reconstruction methods were applied to elucidate the structures of the apices of root vascular cylinders (VCs) in taxa of the Poaceae: Zea mays “Honey Bantam”, Z. mays ssp. mexicana, Hordeum vulgare and Oryza sativa. The primary and nodal roots were investigated. Observations were performed using high-quality sectioning and 3D image-processing techniques improved and developed by the authors. We found that a quiescent uniseriate plerome was located at the most distal part of each VC. Vascular initials were located immediately basipetally to the plerome as a specific uniseriate layer that could be classified into central and peripheral initials that produced all the cells in the VC. No supplying of cells from the plerome to the vascular initials was observed. Numerical analysis revealed a “boundary point” along the root axis where the rate of increase of the vascular cell number markedly declined, and the VC diameter, number of vascular cells, and number of late-maturing metaxylem vessels (LMXs) at that point showed a similar relationship among the taxa and the types of roots examined (primary vs. nodal). The plerome and vascular initials layer can be considered independent after seed germination in these taxa. A boundary point at which procambial cell proliferation sharply declined was identified. The diameters of the VCs, number of LMXs, and number of vascular cells at the boundary point were found to be strongly related to each other.